Expansion of the Tibetan Plateau during the Neogene - Weitao Wang (Nature Portfolio, 2017)
The timing of mountain building along the Tibetan Plateau remains unclear. Here, the authors present new magnetostratigraphic and mammalian biostratigraphic data from sediments to show that mountain building at the edge of the Tibetan Plateau commenced at 25.5 Ma with a separate emergence in the north at 12 Ma.